Protective Efficacy of Cholesterol-Loaded Cyclodextrin (CLC) Against Sperm Morphological Abnormalities in Marwari Stallions - Kumar, Pramod; Mehta, J S; Ravi, S K; Talluri, T R; Kumawat, B L; Kumar, Tapendra; Kumar, Shivendra; Jhamb, D; Dedar, Ramesh Kumar (Animal Reproduction Update, 2023)
The present study aimed to examine the protective potential of cholesterol loaded cyclodextrin (CLC) at varying concentrations against sperm morphological abnormalities of cooled and frozen thawed semen of Marwari stallions. A total of forty eight ejaculates (six stallions and eight ejaculates per stallion) were promptly processed following semen collection and subjected to gross assessment of semen quality attributes. The assessment of sperm morphologies in fresh equine semen was conducted using Eosin and Nigrosine staining technique. The semen samples from individual Marwari stallions were evenly divided into five fractions and incubated in a water bath at 37°C for 15 min after dilution with primary extender to obtain the spermatozoa concentration at 120 × 106 sperm/ml. During incubation, the fractions of every semen sample were exposed to different concentrations of CLC as 0, 1.0, 1.5, 2.0 and 3.0 mg/ml of extender (C, T1, T2,T3, and T4, respectively). All the 5 aliquots were cooled and subsequently subjected to cryopreservation. Each cooled and frozen- thawed (at 37°C for 30 sec) semen samples were analyzed to assess the morphologies of the spermatozoa. Based on the findings, it was concluded that none of the CLC treatment could render any significant protection against the sperm morphological abnormalities at either pre-freeze and/or post-thaw stage of semen samples from Marwari stallions.